Numerical Simulation of an Aortic Flow Based on a HLLC Type Incompressible Flow Solver (Communications in Computational Physics, 2018)
In this study, a three-dimensional artificial compressibility solver based onthe average-state Harten-Lax-van Leer-Contact (HLLC) [13] type Riemann solution isfirst proposed and developed to solve the time-dependent incompressible flow equations. To implement unsteady flow calculations, a dual time stepping strategy including the LU decomposition method is used in the pseudo-time iteration and thesecond-order accurate backward difference is adopted to discretize the unsteady flowterm. Also a third-order accurate HLLC numerical flux is derived for approximatingthe inviscid terms. To verify numerical accuracy, flows over a lid-driven cavity and anoscillating flat plate are chosen as the benchmark tests. In addition, the current solver isextended to solve blood flows in a realistic human aorta measured from MRI (MagneticResonance Imaging). The simulation geometry was derived from a three-dimensionalreconstruction of a series of two-dimensional slices obtained in vivo. Numerical results demonstrate wall stresses were highly dynamic, but were generally high alongthe outer wall in the vicinity of the branches and low along the inner wall, particularly in the descending aorta. The maximum wall stress distribution is presented onthe aortic arch in the systole. In addition, extensive counter-clockwise secondary flowsand three-dimensional helical vortex influenced considerably by the presence of vesselcontraction, torsion and the branches were shown in the descending aorta in the latesystole and early diastolic cycles.